Improvement of an emotional lexicon for the evaluation of beers. (January 2019) - Mora, M.; Giussani, B.; Pagliarini, E.; Chaya, C.
Highlights: An improved consumer-defined emotional lexicon has been generated and tested. Emotional response evoked by beer products has been successfully assessed. The improved lexicon is more user-friendly for consumers. Abstract: Emotional response has been the subject of many studies during the last years. Many studies have shown the importance of using consumers to generate emotional lexicons. Chaya et al. (2015) developed a consumer defined (CD) lexicon to assess emotional response elicited by beer products. Shortly after, van Zyl and Meiselman (2015) presented a procedure to ensure that emotional lists were fully composed by emotions. The present research was developed to improve and test the lexicon developed by Chaya et al. (2015) following the approach proposed by van Zyl and Meiselman (2015). The proposed procedure allowed an easy filtering of terms for the study of emotional response. As a consequence, the test was shorter, clearer, and easier to understand and to complete by consumers. The improved emotional lexicon of beer favoured 1) the efficiency of the research in terms of discrimination among samples, 2) the simplicity of use by the consumers.